Determination of polyols in Bombyx mori larvae by GC-MS measurement - Tlačil, Jan (Jihočeská univerzita, 2018)
Occurrence of various biologically important polyols in the matrix of Bombyx mori larvae was examined. After sample derivatization with silyl reagent the GC-MS analyses were performed. The analytical method was partly validated.
Determination of polyols in Bombyx mori larvae by GC-MS measurement
Keywords: Bombyx; mori; derivatization; silylation; GC-MS measurement; polyols; Bombyx; mori; derivatization; silylation; GC-MS measurement; polyols